Light‐activatable minimally invasive ethyl cellulose ethanol ablation: Biodistribution and potential applications - Jeffrey Yang; Chen‐Hua Ma; John A. Quinlan; Kathryn McNaughton; Taya Lee; Peter Shin; Tessa Hauser; Michele L. Kaluzienski; Shruti Vig; Tri T. Quang; Matthew F. Starost; Huang‐Chiao Huang; et al. (Wiley, 2024)
Abstract While surgical resection is a mainstay of cancer treatment, many tumors are unresectable due to stage, location, or comorbidities. Ablative therapies, which cause local destruction of tumors, are effective alternatives to surgical excision in several settings. Ethanol ablation is one such ablative treatment modality in which ethanol is directly injected into tumor nodules. Ethanol, however, tends to leak out of the tumor and into adjacent tissue structures, and its biodistribution is difficult to monitor in vivo. To address these challenges, this study presents a cutting‐edge technology known as Light‐Activatable Sustained‐Exposure Ethanol Injection Technology (LASEIT). LASEIT comprises a three‐part formulation: (1) ethanol, (2) benzoporphyrin derivative, which enables fluorescence‐based tracking of drug distribution and the potential application of photodynamic therapy, and (3) ethyl cellulose, which forms a gel upon injection into tissue to facilitate drug retention. In vitro drug release studies showed that ethyl cellulose slowed the rate of release in LASEIT by 7×. Injections in liver tissues demonstrated a 6× improvement in volume distribution when using LASEIT compared to controls. In vivo experiments in a mouse pancreatic cancer xenograft model showed LASEIT exhibited significantly stronger average radiant efficiency than controls and persisted in tumors for up to 7 days compared to controls, which only persisted for less than 24 h. In summary, this study introduced LASEIT as a novel technology that enabled real‐time fluorescence monitoring of drug distribution both ex vivo and in vivo. Further research exploring the efficacy of LASEIT is strongly warranted.